ANALISIS SIKAP, KONSISTENSI DAN KEPUASAN PADA TEH KOTAK ULTRAJAYA: AN EXPERIMENTAL MARKETING RESEARCH ON IPB AGRIBUSINESS MASTER OF SCIENCE STUDENTS - Liisa Firhani Rahmasari; Rita Nurmalina; Wahyu Budi Priatna (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2017)
Customer satisfaction is the most important factors that affect the development market of RTD-ready to drink tea industry. Recently, consumer facing several product of ready to drink tea in the middle of tea industry competition, and Teh Kotak Ultrajaya was the pioneer of ready to drink tea in a box. The primary goal of this research is to analyze customer’s attitude of the brand meaning and consistency, secondary goal is to analyze the customer satisfaction toward Teh Kotak Ultrajaya as one of the ready to drink tea product. The research conducted in two countries, Indonesia and Thailand used qualitative and quantitative methods. Fishbein analysis was conducted to measure consumer’s attitude. Customer satisfaction analyzed using the customer satisfaction index (CSI) and importance and performance analysis (IPA). The finding shows that brand meaning and concistency of tea product represented by the unique taste of the tea, satisfaction feeling after consumed it, comfortable with Indonesian brand, and positive experience while in abroad. The result also shows that customers like Teh Kotak Ultrajaya in Thailand better than in Indonesia based on Fishbein score 15,13 in Thailand and 13,80 in Indonesia. Customer satisfaction index (CSI) was also increased from 78,67 percent to 81,67 percent, from satisfied into very satisfied, and there are no atributes in main priority performance to be improved based on IPA yet still has to maintain all of the good atributes on it.